Laminar to turbulent transitions of pipe flows by resonances of natural frequencies of components of test sections - Durst, Franz; Biswas, G.; Haddad, K. (Journal of Turbulence, 2024)
This investigation analyses special papers and doctoral theses that treat transitions of pipe flows as a resonance phenomenon of wave frequencies. These frequencies are natural frequencies of pipe flows, of components of the test section and of vortex ring formations. Resonance conditions are derived that show how the critical Reynolds number, Rec, depends on the volume of the plenum chamber, the pipe diameter, the pipe length, etc. The derived resonance relations were verified experimentally using the experimental data of the third author, yielding (Formula presented.), (Formula presented.) and other interesting results. These findings suggest that the laminar-to-turbulent transition has various modes and transitive dependences. To understand this fully, it is necessary to take all components of the test section involved into account. The test section considered in this paper consists of a mass flow controller to supply the airflow and a plenum chamber, followed by the actual pipe of interest. It is shown that all the components can contribute to the measured value of the critical Reynolds number of pipe flow transition.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Helmholtz resonator; laminar; Pipe flow; transition; turbulent